The Meaning of Indomie's 50 Years of Advertising (Roland Barthes' Semiotic Analysis) - Suci Mardiarini; Muhammad; Fajar Aji (Journal of Art, Film, Television, Animation, Games and Technology, 2023)
The image and the product message shown in the advertisement are spread by relating it to social issues in society and visualized as attractively as possible in the hope that the product can be accepted by a wide audience. This article discusses the meaning in the advertisement of 50 Years of Indomie which is supported by cinematic elements as one of the building elements of an audiovisual work. This research uses Roland Barthes's semiotic theory as the main theory in uncovering hidden meanings in advertising and Thompson and Bowen's cinematographic theory as a supporting theory. The cinematography in this study was used as a vision goggle in watching and reading advertisements for 50 Years of Indomie so that it could support the meaning process carried out. The type of research used in this study is qualitative research supported by descriptive methods. The results of the research obtained in the form of advertisements 50 Years of Indomie try to instill the myth that Indomie is a food product that must always be present and enjoyed anytime and anywhere, thus making Indomie an instant noodle product that always accompanies every situation in the lives of Indonesians and abroad. In addition, there is also the Ideology of Consumerism and the Ideology of Class and Racial Equality that seeks to be infiltrated behind this 50 Years of Indomie advertisement.